Study on an improved naive Bayes algorithm in spam filtering - Lei YANG; Cui-ling CAO; Jian-guo SUN; Li-guo ZHANG (Tongxin xuebao, 2017)
A method of improved support vector machine naive Bayes algorithm was proposed——TSVM-NB algorithm.